2016
DOI: 10.1093/abbs/gmv128
|View full text |Cite
|
Sign up to set email alerts
|

Targeting AMPK signaling in combating ovarian cancers: opportunities and challenges

Abstract: The development and strategic application of effective anticancer therapies have turned out to be one of the most critical approaches of managing human cancers. Nevertheless, drug resistance is the major obstacle for clinical management of these diseases especially ovarian cancer. In the past years, substantial studies have been carried out with the aim of exploring alternative therapeutic approaches to enhance efficacy of current chemotherapeutic regimes and reduce the side effects caused in order to produce … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 199 publications
(302 reference statements)
2
17
0
Order By: Relevance
“…Therefore, it was hypothesized that ATP levels may be lower in p53 -/cells due to uncontrolled rapid cell proliferation and growth, which may cause much higher consumption of ATP. ATP depletion is the main signal that induces AMPK activation by phosphorylation of Thr172 (44)(45)(46). The present study demonstrated that serum starvation markedly increased phosphorylation of AMPK at Thr172 in HCT116 p53 -/cells compared with in HCT116 p53 +/+ cells.…”
Section: Ampk Activation Is Increased In P53 -/Cells Under Serum Starsupporting
confidence: 51%
“…Therefore, it was hypothesized that ATP levels may be lower in p53 -/cells due to uncontrolled rapid cell proliferation and growth, which may cause much higher consumption of ATP. ATP depletion is the main signal that induces AMPK activation by phosphorylation of Thr172 (44)(45)(46). The present study demonstrated that serum starvation markedly increased phosphorylation of AMPK at Thr172 in HCT116 p53 -/cells compared with in HCT116 p53 +/+ cells.…”
Section: Ampk Activation Is Increased In P53 -/Cells Under Serum Starsupporting
confidence: 51%
“…This leads to a change in the ATP‐to‐AMP ratio and canonical AMPK activation. It inhibits cell growth through suppressing mTOR signaling . In this context, it is possible that metformin inhibits HKII‐PDK1 loop via suppressing AMPK/mTOR .…”
Section: Discussionmentioning
confidence: 99%
“…It inhibits cell growth through suppressing mTOR signaling. 44,45 In this context, it is possible that metformin inhibits HKII-PDK1 loop via suppressing AMPK/mTOR. 46 Additional studies are needed to determine whether the role of metabolism in chemoresistance in OVCA is histologic subtypedependent.…”
Section: Discussionmentioning
confidence: 99%
“…The AMP-activated protein kinase (AMPK), a cellular metabolic sensor, participates in maintaining energy homeostasis under external stresses in multiple human cancers. 129 The AMPK, expressed extensively in all eukaryotic cells, comprises of a catalytic subunit (α) and two regulatory subunits (β and γ). 130 , 132 According to different inputs, outputs, functions, and sub-cellular localizations, a total of 12 potential AMPK complexes were assembled by various isoforms of each subunit.…”
Section: Roles Of Main Signaling Pathways In Aerobic Glycolysismentioning
confidence: 99%